The study on the effectiveness of management system towards employees productivity at SESB Kota Kinabalu / Yusrafie Hussein - Hussein, Yusrafie (2008)
This study is entitled "THE STUDY ON THE EFFECTIVENESS OF MANAGEMENT SYSTEM TOWARDS EMPLOYEES' PRODUCTIVITY AT SESB KOTA KINABALU"